The influence of particle size and curing conditions on testing mineral trioxide aggregate cement - William Nguyen Ha; Bill Kahler; Laurence James Walsh (Medical Journals Sweden, 2016)
Objectives: To assess the effects on curing conditions (dry versus submerged curing) and particle size on the compressive strength (CS) and flexural strength (FS) of set MTA cement. Materials and methods: Two different Portland cements were created, P1 and P2, with P1 < P2 in particle size. These were then used to create two experimental MTA products, M1 and M2, with M1 < M2 in particle size. Particle size analysis was performed according to ISO 13320. The particle size at the 90th percentile (i.e. the larger particles) was P1: 15.2 μm, P2: 29.1 μm, M1: 16.5 μm, and M2: 37.1 μm. M2 was cured exposed to air, or submerged in fluids of pH 5.0, 7.2 (PBS), or 7.5 for 1 week. CS and FS of the set cement were determined using a modified ISO 9917-1 and ISO 4049 methods, respectively. P1, P2, M1 and M2 were cured in PBS at physiological pH (7.2) and likewise tested for CS and FS. Results: Curing under dry conditions gave a significantly lower CS than when cured in PBS. There was a trend for lower FS for dry versus wet curing. However, this did not reach statistical significance. Cements with smaller particle sizes showed greater CS and FS at 1 day than those with larger particle sizes. However, this advantage was lost over the following 1-3 weeks. Conclusions: Experiments that test the properties of MTA should cure the MTA under wet conditions and at physiological pH.